Pengaruh Stres Terhadap Emotional Eating pada Atlet Arung Jeram Jawa Timur - Estri Novia Febrianti; Miftakhul Jannah (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This study aims to analyze the effect of stress on emotional eating among whitewater rafting athletes in East Java. Stress, caused by the demands of competition and intensive training, often triggers emotional eating behavior, which involves overeating as a response to negative emotions. This research employs a quantitative approach with a cross-sectional design, involving 68 athletes from the East Java Whitewater Rafting Federation. Data were collected through an online questionnaire using a stress scale and an emotional eating scale. The results show that the majority of athletes (70.6%) experience high levels of stress, and most (39.7%) exhibit moderate levels of emotional eating. Regression analysis indicates a significant positive relationship between stress and emotional eating (p < 0.05), with stress contributing 9.2% to the variation in emotional eating. This study highlights the importance of stress management to prevent emotional eating, which can affect athletes' health and performance. Recommended stress management strategies include emotional regulation training and providing psychological counseling services.